2014
DOI: 10.1098/rspb.2013.1834
|View full text |Cite
|
Sign up to set email alerts
|

Retirement investment theory explains patterns in songbird nest-site choice

Abstract: When opposing evolutionary selection pressures act on a behavioural trait, the result is often stabilizing selection for an intermediate optimal phenotype, with deviations from the predicted optimum attributed to tracking a moving target, development of behavioural syndromes or shifts in riskiness over an individual's lifetime. We investigated nest-site choice by female golden-winged warblers, and the selection pressures acting on that choice by two fitness components, nest success and fledgling survival. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 46 publications
1
55
1
Order By: Relevance
“…This is not to suggest that Golden-winged Warblers breeding in shrub wetlands do not use trees or high-canopy areas but rather establish defended territories in highest densities within shrub wetlands with fewer trees in their interiors; it seems likely that Goldenwinged Warblers nesting within shrub wetlands may forage in mature canopy trees around the peripheries of these habitats. Furthermore, breeding in association with ecotonal habitat may not only provide quality foraging opportunities (Bellush et al 2016, Frantz et al 2016) but perhaps even improve lifetime fitness through high rates of nesting success and/or access to quality postfledging habitat (Streby et al 2014). In contrast to the densitycanopy relationship described here, studies of the species within managed uplands have found the opposite trend suggesting that Golden-winged Warblers use areas with moderate canopy cover within those community types (Patton et al 2010, Roth et al 2014.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This is not to suggest that Golden-winged Warblers breeding in shrub wetlands do not use trees or high-canopy areas but rather establish defended territories in highest densities within shrub wetlands with fewer trees in their interiors; it seems likely that Goldenwinged Warblers nesting within shrub wetlands may forage in mature canopy trees around the peripheries of these habitats. Furthermore, breeding in association with ecotonal habitat may not only provide quality foraging opportunities (Bellush et al 2016, Frantz et al 2016) but perhaps even improve lifetime fitness through high rates of nesting success and/or access to quality postfledging habitat (Streby et al 2014). In contrast to the densitycanopy relationship described here, studies of the species within managed uplands have found the opposite trend suggesting that Golden-winged Warblers use areas with moderate canopy cover within those community types (Patton et al 2010, Roth et al 2014.…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, Golden-winged Warbler affinity for edge habitat is also somewhat intuitive; Golden-winged Warblers are known to often incorporate mature forest edges into their territories (Hunter et al 2001, Patton et al 2010, especially within shrub wetlands where they may actually require edges (Rossell et al 2003). Although our study did not examine the drivers behind these patterns, Rossell et al (2003) suggested that Golden-winged Warblers within shrub wetlands may place nests near edges and edges are known to be relevant to the nesting ecology of this species (Patton et al 2010, Streby et al 2014.…”
Section: Discussionmentioning
confidence: 47%
“…Furthermore, we found no evidence that saltmarsh and Nelson's sparrows exhibit differences in two life history traits that could result in patterns of fecundity that differ from those observed in nest survival probabilities (renesting rate and clutch size). Thus, nest survival is likely a reasonable index of the fitness consequences of oviposition divergence in this system and a better index than has been reported in other songbirds (Streby and Andersen 2013;Streby et al 2014). …”
Section: Discussionmentioning
confidence: 94%
“…We did not include lateral vegetation cover or canopy cover in candidate models because neither of these variables was found to be significant in a previous analysis (Streby et al 2014). We produced 24 candidate models using all relevant combinations of variables and ranked models using Akaike's Information Criterion corrected for small sample size (AIC c ; Burnham and Anderson 2002).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Significant population declines over the last 50 years have been linked to habitat loss (Confer et al 2011). Goldenwinged Warbler nest success is strongly influenced by nest location, with nest success increasing with distance into shrubland and away from edges (Streby et al 2014). Unbiased information about nesting habitat use and nest productivity is necessary to inform and improve management across the species' breeding range.…”
Section: Study Speciesmentioning
confidence: 99%